ONLINE TRACER STUDY OF BUNG HATTA UNIVERSITY (GEOMATE Journal, 2016)
This research serves as the basis to design an online graduate tracking system needed by Bung Hatta University to meet the standards required by National Accreditation Board of Higher Education Institutions of Indonesia (BAN-PT) and the University stakeholders. The system, which is called Tracer Study, is programmed by using PHP and MySQL programming languages and by applying CMS Bootstrap. There are four actors/elements involving in the Tracer Study, namely: Graduates/Alumni, Employers of the Graduates, University Official, and Administrator of the System. The system applies waterfall method with several stages of processing, namely analysis, designing, coding, testing, and maintenance. The design of Tracer Study has already been tested at small scale within the circle of the Faculty of Teacher Training and Education and is currently applied at big scale by uploading the same at the website of Bung Hatta University after obtaining the approval of University official.